(E)-1-Ferrocenyl-3-[2-(2-hydroxyethoxy)phenyl]prop-2-en-1-one - Raghavachary Raghunathan; P. R. Seshadri; Santhanagopalan Purushothaman; S. Paramasivam (Acta Crystallographica Section E, 2013)
In the title compound, [Fe(C5H5)(C16H15O3)], the cyclopentadienyl rings are in an eclipsed conformation and the benzene ring makes dihedral angles of 10.84 (9) and 12.35 (9)°, respectively, with the substituted and unsubstituted cyclopentadienyl rings. In the crystal, molecules form inversion dimers through pairs of O—H...O hydrogen bonds. Weak C—H...O hydrogen bonds are observed between the dimers.